Peran Pesantren Dalam Melestarikan Bahasa Arab Sebagai Bahasa Ilmu Dan Ibadah - Fahrurohman, Wiyan Zendi; Ahmadi , Ahmadi (Jurnal Naskhi Jurnal Kajian Pendidikan dan Bahasa Arab, 2025)
This research discusses the role of Pondok Pesantren Modern Al-Anwar in preserving Arabic as the language of science and worship. Arabic has an important position in Islam, especially as the main language in the Qur'an and Hadith. Therefore, mastering Arabic is a necessity for students in understanding Islamic teachings in depth. Modern Al-Anwar Islamic Boarding School implements various programs to improve Arabic language skills, such as muhadhoroh (speech practice), muhadasah (daily conversation), imlak and istimak learning, and reading the yellowclassical books. In addition, this pesantren also requires the use of Arabic in daily life to create a conducive learning environment. The research method used is descriptive qualitative with observation, interview, and documentation techniques. The results showed that the strategies applied by Pondok Pesantren Modern Al-Anwar are effective in improving the students' mastery of Arabic as well as maintaining the role of Arabic in Islamic education